Isocoumarin derivatives from the marine-derived fungus Phoma sp. 135. Issue 3 (20th January 2016) - Elsebai, Mahmoud F.; Ghabbour, Hazem A.
Graphical abstract: Abstract: The dihydro-isocoumarin derivatives1 –2 were isolated from the marine-derived fungus Phoma sp. 135. Structural elucidation was achieved through extensive spectroscopic evaluation including 1D- and 2D-NMR, accurate mass measurements, and single crystal X-ray diffraction analysis. We report herein the structure and absolute configuration of the known compound1 using X-ray diffraction, and the structural elucidation of the new dihydro-isocoumarin derivative2 .